La inteligencia emocional y su relación con el aprendizaje del idioma inglés en niños de 4 a 5 años en preescolar - Quishpe Hipo, Luis Armando; Rojas Yumisaca, Wilson Gonzalo (Dominio de las Ciencias, 2021)
Emotional Intelligence is part of the experience of all human beings during their life, for that reason children as well as adults suffer various emotions in their daily lives every day, such as: fear, shame, cheerfulness, sadness, empathy, anger, among others. The objective was to determine the incidence of emotional intelligence in English Language learning in children between 4 and 5 years of age form Pre-Kinder, from Leonardo da Vinci Educational Unit, Riobamba, Ecuador. The study was a non-experimental investigation of a transectional-descriptive type with a mixed approach, applying field and documentary research, which modality was socio-educational. The population consisted of 56 children, 29 girls and 27 boys. The observation technique and the notebook instrument were applied to gather information. The information was compiled in a database and analyzed through descriptive statistics. The non-parametric Chi-square test (X2) was applied to verify the hypothesis using the SPSS software. The results were illustrated in graphs with mathematical values. The statistical value of the Chi-square test was X2cal = 4.158 < X2tab = 11.070, with 5 df y with a value of Î±=0.05. In conclusion, the Chi-square test rejected the Null Hypothesis (Ho), accepting the Alternative Hypothesis (H1) because the calculated value of Chi-square is less than the critical value of Chi-square with 5 degrees of freedom and with a significant level of 0.05. In conclusion, the Emotional Intelligence variable is associated with the English Language Learning variable, where the emotion of fear (19.64%) being the most frequent in social talk, followed by shame (14.28%) in private talk.